Sustainability and financial assessments and double-criteria optimization of a novel power/hydrogen coproduction scheme using solar power and compressed air energy storage cycle - Cao, Yan; Mansir, Ibrahim; Mouldi, Abir; Alsharif, Sameer; A. Aly, Ayman; Jarad, Fahd; Batcha, M. F. M.; Bouallegue, B. (Elsevier, 2022)
The use of solar energy is vital for the future of meeting the energy demand in the world. Different high- or medium-temperature solar-based power plants have been introduced and examined; however, the low exergetic performance of the solar power-to-electricity process is the principal defect. Although using thermal energy storage in such plants leads to continuous production throughout the day, it also increases the rate of exergy destruction. To improve this deficiency, the present study suggests and studies the simultaneous use of thermal energy storage and compressed air energy storage technologies in a high-temperature soar-based coproduction system by considering a multi heat recovery technique. In this regard, the operation of the system is divided into three periods of the day, namely, storing (low-radiation mode), charging (high-radiation mode), and discharging (night times). Hence, a Brayton cycle equipped with a high-temperature solar field using heliostat mirrors is established. In addition, an organic Rankine cycle is employed for heat recovery. In addition, a low-temperature electrolyzer is utilized for hydrogen generation. The ability of the suggested framework is investigated from the exergetic, sustainability, and financial aspects and is optimized by an advanced evolutionary algorithm. The optimum state indicates that the objective functions, i.e., exergetic round trip efficiency and unit cost of the system, are 26.17% and 0.159 $/kWh, respectively. Furthermore, the electricity capacity and hydrogen production rate are obtained at 7023 kW and 627.1 kg/h, respectively. Moreover, its sustainability index and exergoenvironmental impact index are found at 1.66 and 2.30, respectively.